Growth Performance and Nutrient Uptake of Oil Palm Seedling in Prenursery Stage as Influenced by Oil Palm Waste Compost in Growing Media - A. B. Rosenani; R. Rovica; P. M. Cheah; C. T. Lim (International Journal of Agronomy)
The use of composted oil palm wastes in the oil palm nursery as an organic component of growing medium for oil palm seedlings seems promising in sustainable oil palm seedling production. This study was conducted to investigate the effects of six oil palm waste compost rates (0, 20, 40, 60, 80, and 100%) on the growth performance of oil palm seedling and nutrient uptake in the prenursery stage (0–3 months). The addition of oil palm compost reduced the soil bulk density (1.32 to 0.53 g cm−3) and increased soil pH (4.7 to 5.1) of growth media. Oil palm waste compost treatment produced positive growth performance up to 70%. A regression analysis indicated in 72% of compost and topsoil mixture as a polybag growth medium was optimum in producing best growth performance of oil palm seedling in the prenursery stage. Foliar analysis implied highest nutrients uptake (N, P, K, Mg, Ca, Fe, Zn, and Cu) for seedlings grown in 60 to 100% compost media.